Issues and Concerns in the Implementation of the Students’ Information System - Gamao, A O; Rebortera, M A (KnE Social Sciences, 2018)
This study explored issues and concerns in the implementation of the Students’ Information System (SIS). Employing purposive sampling, nine (9) key informants composed of students representing the following: Bachelor Science in Information Technology (BSIT), Bachelor of Science in Marine Biology (BSMB), Bachelor in Public Administration (BPA), Bachelor in Secondary Education (BSE), Bachelor of Science in Fisheries (BSFi), Bachelor of Science in Food Technology (BSFT), Supreme Student Council (SSC), Davao Reef (DR), Scholars were selected in this study. Data gathered through in-depth interview using the enhanced interview guide were coded, analysed, and clustered into themes. Findings revealed that issues and concerns were generally clustered as: 1.) Lack of End-Users’ Training, 2.) Lack of Enthusiasm, 3.) Unavailability of the System, 4.) Lack of Technical Support, 5.) Difficulty to Register Accounts, 6.) No Proper Notice Posted, 7.) Unsuitable Location,8.) Need for System Enhancement, 9.) Lack of Maintenance, 10.) Need for Additional Kiosks, 11.) Inaccuracy of Account Details, and 12.) Need for Alternative System. Results likewise disclosed the experiences of end-users have something in common. Hence, these entail tailored-fit responses to achieve the desired outcomes. The said controversies are rooted from diverse factors in the implementation of the developed software and developer plays a significant role in addressing matters to deliver the expected services and draw better implementation of the SIS. The Institute of Information Technology in its quest for quality and relevance may consider the issues and concerns that emerged in this study for enhancing the deployed SIS for better service to students. Keywords: Issues and concerns, Student Information System, Institute of Information Technology